The nudge deck: A design support tool for technology-mediated nudging - Caraban, Ana; Konstantinou, Loukas; Karapanos, Evangelos (My University, 2020)
The idea of nudging - that subtle changes in the 'choice architecture' can alter people's behaviors in predictable ways - was eagerly adopted by HCI researchers and practitioners over the past decade. Yet, the design of effective nudging interventions is far from trivial, with theoretical knowledge being unstructured, with over a hundred cognitive biases found online, and inaccessible to practitioners during design meetings. We present the design and evaluation of the Nudge Deck, a card-based, design support tool that provides actionable knowledge for the design of technology-mediated nudges. The tool was evaluated through two case studies where 58 participants were asked to design nudging interventions, in the contexts of physical activity promotion and misinformation mitigation, with and without the cards. We report on how the cards enhanced designers' self-efficacy, and led to more theoretically grounded, creative and appropriate for the context, ideas.
Keywords: Nudging; Behavior Change; Persuasive Technology